СХІДНОСЛОВ'ЯНСЬКА МІФОЛОГІЯ І ЗВИЧАЄВЕ ПРАВО: ІНТЕГРАЦІЙНІ КОНЦЕПТИ - Грищенко, Н. В. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
У статті прослідковано зв'язок міфології і звичаєво-правових норм, проаналізовано народно-світоглядний підтекст таких термінів звичаєвого права, як «рота», «видача на потік», «ордалії», тощо,обгрунтовано положення про значення сакралізації права.Грищенко Н.В. Восточнославянская мифология и обычное право: интеграционныеконцепты. В статье рассматриваются интеграционные концепты мифологии и обычного права,исследуются народно-мировоззренческие составляющие таких понятий обычного права, как «рота»,«выдача на поток», «ордалии» и др., расскрывается значение сакрализации права.Ключевые слова: мифология, символ, обычное право, интеграционный концепт, доказательство.Grishchenko N.V. The East Slavic mythology and the Customary Law: integration concepts. Thearticle examined the link of mythology and customary legal norms, analyzed national ideological implications ofsuch terms of customary law as "rota" (meaning: oath, swear), "delivery of a stream" (meaning: exclusion fromthe guardianship of family), "ordaliyi" (meaning: trial) etc.. Involving study of Ukrainian literature, the authorargues that under the influence of the East Slavic mythology in customary legal practice fixated using such"transcendental" evidence, as the oath with calling of God's name to witnesses, trial by fire (hot iron), water,"efficiency of land under turf", etc. The most revered elements by pagan – soil, fire, water, integrating incustomary and legal plane started acted as witnesses of criminal acts, detect violators. Such evidence ofmythological character considered authoritative and final, and the decisions taken by their participation, had notsubject to any appeal, because it was made by deities.The author shows that braiding of sacred motifs in common, the legal framework provided firstnorms ofholiness and turned them into unquestionable authoritative requirements. Mythological representation correlatedwith deep, subconscious levels of the human psyche. Statutory requirements that were based on them wereunconsciously-authoritarian in nature and did not cause any doubt, do not allow criticism and not subject torefutation. As a result, the common law has been turned, on the one hand, to the sacred forces, on the other handtoa real life. The East Slavic Mythology performed a source of constant updating requirements of customary lawand ensuring its high social status. As a result of the study the author concludes that in order for people toperceive, respected and fulfilled the law, they should be subject not only of knowledge but also of faith.Key words: mythology, symbol, customary law, integration concepts, evidence.